Effect of Disorder Induced by Ball Milling on the Electrochemical Performance of Catalytically Graphitized Carbon Xerogel as Anode for Lithium Ion Batteries. (7th August 2015) - Gopalakrishna, Karthik Mamandur; Kakunuri, Manohar; Sharma, Chandra Shekhar
Abstract : We have synthesized resorcinol formaldehyde based carbon xerogel (RFCX) by graphitizing it at 1800 °C in the presence of a catalyst. As-synthesized RFCX was then ball milled for different duration to develop a control on its microstructure as studied in detail using scanning electron microscopy, X-ray diffraction, BET surface area and transmission electron microscopy. Structural characterization revealed that RFCX is an example of hard carbon and with the increase in milling time, there was an increase in its structural disorder further. This increase in structural disorder was then correlated to understand the electrochemical behaviour of RFCX using cyclic voltammetry and galvanostat charge/discharge measurements. RFCX sample ball milled for 4 h showed significant increase in its reversible capacity (310 mAh/g) with 99.1% coulombic efficiency after 50 cycles. Further this change in microstructure of RFCX facilitated their use at high C-rate (up to 1 C) with excellent capacity retention. This work paves the way of efficient use of RFCX as an anode material for next generation lithium ion batteries.